The relationship between subjective compliance with isolation precautions and moral sensitivity in novice nurses: cross-sectional study - Hanife Tiryaki Şen; Şehrinaz Polat; Leyla Afşar Doğrusöz (BMC, 2024)
Abstract Background Increasing compliance with isolation precautions is important in reducing hospital-acquired infections and their consequences. It is not possible to achieve and maintain nurse compliance through supervision, control, pressure, or training. Therefore, nurses must personally demand compliance with isolation precautions. This study aimed to determine the relationship between compliance with isolation precautions and the moral sensitivity levels of nurses who have just started working. Methods This study employed a descriptive and cross-sectional research design. The study population consisted of 456 new nurses recruited during the pandemic. All of the new nurses who volunteered to participate in the study and completed the questionnaires completely were included in the study and 398 nurses constituted the sample of the study. Data were collected from 398 out of 456 novice nurses who agreed to participate in the study. The population coverage rate was 87.28%. Participants were selected using convenience sampling method. The data collection tools included an Introductory Information Form, The Isolation Compliance Precautions Scale (TIPCS), and the Moral Sensitivity Questionnaire (MSQ). Descriptive statistics, correlation analyses, and regression models were used to analyze data. Findings The mean score of the MSQ was high (mean ± SD = 90.49 ± 25.94; median (P25-P75) = 84 (range, 74-97), and the score for TIPCS was high (mean ± SD = 79.29 ± 7.68; median (P25-P75) = 82 (range, 76-85)). No correlation was found between MSQ and TIPCS (p > 0.05). According to the regression analysis, although the MSQ did not correlate with TIPCS, compliance with isolation measures was found to increase as the conflict subscale of moral sensitivity increased (β= -0.36, CI= -0.55 to -0.16; p < 0.001). Choosing the profession willingly had a positive correlation with compliance with isolation measures (β = 5.3, CI = 2.4 to 8.3; p < 0.001). In addition, starting the profession at an early age had a positive correlation with compliance with isolation measures (β= -0.49, CI= -0.8 to -0.17; p = 0.002). Conclusion The conflict sub-dimension of moral sensitivity is an important factor in nurses' compliance with isolation measures, and conducting necessary training and other studies to improve nurses' moral sensitivity may increase their compliance with isolation measures.